(untitled) (Bangladesh Journal of Plant Taxonomy, 2015)
Sonerila gadgiliana, a new species collected from high altitude moss-covered dripping rocks of grassland-shola margins in Wayanad district, Kerala, India is described and illustrated. The species resembles S. raghaviana Ratheesh et al., S. rotundifolia Bedd. and S. veldkampiana Ratheesh et al., but differs from leaf, inflorescence, peduncle, hypanthium, petal, anther, capsule and seed characteristics. Bangladesh J. Plant Taxon. 22(1): 915, 2015 (June)